2021
DOI: 10.2495/cmem-v9-n2-117-125
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of gears: An innovative hybrid FEM–analytical approach

Abstract: Gearboxes are widely used in several applications ranging from the automotive to the industrial and robotic sectors. A planetary gearbox is a special kinematic gear arrangement that, taking advantage of a planet carrier, ensures high reduction ratios together with a very small design. Therefore, they are widely employed for transmissions which require a high power density. There are several fields of applications including, but not limited to, mechatronic, automation and wind power generation. To improve the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…After obtaining the responses of the system in healthy and damaged conditions, it was observed that specific frequencies, between the range of 0 Hz and 8500 Hz, due to the harmonics considered in this work, shift given the presence of damage [50]. Indeed, the results in terms of signals from the healthy system could be validated with the signals from the experimental test.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…After obtaining the responses of the system in healthy and damaged conditions, it was observed that specific frequencies, between the range of 0 Hz and 8500 Hz, due to the harmonics considered in this work, shift given the presence of damage [50]. Indeed, the results in terms of signals from the healthy system could be validated with the signals from the experimental test.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, in order to generate good numerical results and obtain converged simulations, the flanks in the region of the gear teeth, where the main analysis take place, must be discretized with a very fine mesh. This is usually performed due to the contact position of the gears and the variation of their engaged surfaces during operation, which increases the number of equations to be solved [50]. Thus, this problem can be solved in the T3D environment.…”
Section: Modeling Implementation and Numerical Simulationmentioning
confidence: 99%
“…In the realm of precision machinery, attention is consistently directed toward the performance and efficiency of transmission systems, as underscored by a wealth of scholarly inquiry [1,2]. Gears, pivotal mechanical components within these systems, are recognized as bearing a substantial portion of the power load [3][4][5][6][7][8][9][10][11][12][13]. It has been observed that during their operation, the heat generated from interactions such as meshing, sliding, and impact with adjacent gears plays a significant role in influencing the system's stability and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors use the vibrational response of the gearboxes as a trigger for detecting damage. In this regard, Concli et al [13] proposed a model of a back-to-back test rig and of a planetary gearbox [14] based on the same hybrid Finite Element (FE)-the analytical approach used in this paper. The comparison of the vibrational spectra predicted, and the experimental measurements performed at Politecnico di Milano, have fully validated the approach.…”
Section: Introductionmentioning
confidence: 99%